Odourless Strategy for Deep Eutectic Solvent-Mediated Ring Opening of Epoxides with In Situ Generated S-Alkylisothiouronium Salts - Azizi, Najmedin; Yadollahy, Zahra; Rahimzadeh-oskooee, Amin (Synlett, 2014)
A general, straightforward and odourless ring-opening reaction allows the preparation of β-hydroxy sulfides from in situ generated S-alkylisothiouronium salts in urea–choline chloride-based deep eutectic solvent (DES). In addition, reaction of epoxides with thiourea in DES yields the corresponding thiiranes.
Keywords: deep eutectic solvent; epoxide; odourless thiol chemistry